Specialized Pro-Resolving Mediators as Potential Regulators of Inflammatory Macrophage Responses in COVID-19 - Balta, Maria G.; Papathanasiou, Evangelos; Christopoulos, Panagiotis F. (Frontiers in Immunology, 2021)
The recent outbreak of SARS-CoV2 has emerged as one of the biggest pandemics of our century, with outrageous health, social and economic consequences globally. Macrophages may lay in the center of COVID-19 pathogenesis and lethality and treatment of the macrophage-induced cytokine storm has emerged as essential. Specialized pro-resolving mediators (SPMs) hold strong therapeutic potentials in the management of COVID-19 as they can regulate macrophage infiltration and cytokine production but also promote a pro-resolving macrophage phenotype. In this review, we discuss the homeostatic functions of SPMs acting directly on macrophages on various levels, towards the resolution of inflammation. Moreover, we address the molecular events that link the lipid mediators with COVID-19 severity and discuss the clinical potentials of SPMs in COVID-19 immunotherapeutics.